The Effect of Applying the Archerys ID Model Instructional Design and Learning Motivation on Physics Learning Outcomes at SMAN 4 Batam - Fiona; Darmansyah; Zulhendri Zen; Fetri Yeni J; Emilham Mirshad; Abdul Habib Arrasyidi Desky (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to examine the effect of implementing the Archerys ID Model instructional design and student learning motivation on physics learning outcomes. The Archerys ID Model, developed from the ARCS motivational framework, incorporates reflection and the formation of learning habits to enhance both engagement and academic integrity. A quasi-experimental method with a 2×2 factorial design was employed, involving an experimental group taught using the Archerys ID Model and a control group using the TPACK model. Data were collected through learning motivation questionnaires and standardized physics tests, then analyzed using two-way ANOVA to assess main effects and interactions. The results showed that students taught with the Archerys ID Model achieved significantly higher learning outcomes than those in the TPACK group. Learning motivation also had a significant effect on student performance, while no interaction was found between the instructional model and motivation levels. These findings indicate that the Archerys ID Model is effective in improving learning outcomes, particularly when combined with strategies that promote intrinsic learning engagement.